Sustancias alternativas para el control del caracol africano (Achatina fulica) en el Valle del Cauca, Colombia (2016)
The presence of the giant African snail Achatina fulica (Bowdich 1822) was confirmed in Colombia in 2008. Due to economic and health implications of this species and the difficulties in controlling it, it is essential to establish the relevance of protocols and alternative inexpensive substances used to control the snail. In this research, the effectiveness of manual removal and manual removal with spray of calcium oxide was analyzed. Both techniques had similar efficiencies, so it is recommended that calcium oxide should be implemented only for the disposal of the collected individuals in order to reduce costs and decrease the impact on arthropofauna. In addition, we evaluated the molluscicide ability of commercial sodium hypochlorite, two plant extracts (Tabebuia rosea and Jatropha curcas), and commercial molluscicide (metaldehyde). We found that the three alternative substances were effective as molluscicides, but with lower effectiveness than the commercial substance. Implementation of the extracts of T. rosea and J. curcas is recommended because they have low cost, and do not present negative effects on the environment.